How a Language Laboratory Improves the Teaching-Learning Process in the “San Rafael” Salesian Technical High School of Esmeraldas City in 2013 - Medina Mariduena, Xiomara Elizabeth (2014)
Medina Mariduena, Xiomara Elizabeth\; 'How a Language Laboratory Improves the Teaching-Learning Process in the “San Rafael” Salesian Technical High School of Esmeraldas City in 2013' 87 p. 'Tesis - Licenciatura en Lingüística Aplicada con mención en Enseñanza de Inglés